2021
DOI: 10.3389/fimmu.2021.630096
|View full text |Cite
|
Sign up to set email alerts
|

Club Cell Loss as a Feature of Bronchiolization in ILD

Abstract: Background: Distal airway metaplasia may precede honeycombing in progressive fibrosing interstitial lung disease (ILD). The SCGB1A1+ bronchiolar-specific club cell may play a role in this aberrant regenerative process.Objective: To assess the presence of club cells in the small airways of patients suffering from ILD.Methods: Small airways (internal diameter <2 mm) in lung samples [surgical lung biopsy (SLB) and/or transbronchial lung cryobiopsy (TBLC)] from 14 patients suffering from ILD and 10 controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(26 reference statements)
2
7
0
Order By: Relevance
“…We also detected changes in the airway epithelium which were mostly driven by time rather than differences between PC groups. However, a common feature of IPF is the ectopic appearance of airway epithelial cells (bronchiolization), and their secretion of CC16/SCGB1A1 particularly in Club cells [39][40][41][42] . We had observed that similarly to IPF, some images from PC patients showed extensive secreted CC16 in peribronchial regions (Figure 2l).…”
Section: Derangement Of Vascular and Epithelial Lung Structure In Pc ...mentioning
confidence: 99%
“…We also detected changes in the airway epithelium which were mostly driven by time rather than differences between PC groups. However, a common feature of IPF is the ectopic appearance of airway epithelial cells (bronchiolization), and their secretion of CC16/SCGB1A1 particularly in Club cells [39][40][41][42] . We had observed that similarly to IPF, some images from PC patients showed extensive secreted CC16 in peribronchial regions (Figure 2l).…”
Section: Derangement Of Vascular and Epithelial Lung Structure In Pc ...mentioning
confidence: 99%
“…In IPF samples, LGR6 expression was generally increased in the basal progenitor populations, reaching the highest protein levels in areas of bronchiolization and honeycombing, whereas in COPD tissues, LGR6-positive basal cells were observed in damaged and inflated bronchioles and in proliferative bronchiolar lesions, but not in airways proximal to emphysematous lesions. The presence of LGR6 in lung epithelial progenitors of damaged and proliferating bronchioles and in fibrotic alveoli may suggest a Wnt-mediated response in divergent chronic insults occurring in COPD and IPF [ 10 , 46 , 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The population of club cells in the fibrotic tissue of patients with ILD is different and apparently more heterogeneous compared to that of healthy subjects. Some authors have found less club cells (identified by the SCGB1A1+ marker) in the small airways of ILD, particularly in areas with a UIP radiological pattern [66], and have explained the bronchiolization process by the migration of club cells to more proximal sites in the airways or by the blockade in replacement of these cells after lung injury.…”
Section: Modulation Of the Fibrotic Processmentioning
confidence: 99%